Serial sampling reveals temperature associated response in transcription profiles and shifts in condition and infectious agent communities in wild Atlantic salmon. (14th September 2021) - Chapman, Jacqueline M.; Lennox, Robert J.; Twardek, William M.; Teffer, Amy K.; Robertson, Martha J.; Miller, Kristi M.; Cooke, Steven J.
Abstract: Anadromous Atlantic salmon ( Salmo salar ) populations have declined across their Southern distributions in North America. While river temperature has been identified as a central factor influencing migration behavior and over‐winter survival, little research has addressed the prevalence of infectious agents in wild Atlantic salmon populations. Further, current understanding of how temperature may interact with fish condition to influence infection outcomes in the wild is limited. The objective of this research was to characterize the change in individual condition and pathogen dynamics as salmon acclimatized to the freshwater environment during the spawning migration. Serial individual sampling (non‐lethal gill biopsy and microwave fatmeter readings) was accomplished by repeated capture and release of 27 marked individuals, which revealed how lipid content, infectious agent prevalence and relative loads, and stress and osmoregulatory transcripts changed during the initial month of their annual spawning migration. Relative infection burden (a composite metric representing the overall pathogen profile) and transcription profiles were modeled with freshwater residency, river temperature, and lipid content. Infectious agents Tetracapsuloides bryosalmonae, Candidatus Branchiomonas cysticola, Flavobacterium psychrophilum, Paranucleospora theridion, and Piscichylamidia salmonis were detected in the population. Relative infection burden and microbial pathogen species richness increased over the course of the study. Water temperature and time since fresh water entry were related to salmon transcriptional response, but not relative infection burden, highlighting the metabolic cost associated with warming temperatures and dynamic nature of pathogen infection profiles in migratory fish species. This work is the first to provide a comprehensive screening of microbial pathogen species in wild Atlantic salmon in the region, and the first to employ a unique study design that facilitates serial sampling without imposing holding stress. The high prevalence and relative load of T. bryosalmonae observed may demonstrate increased exposure to transmission pathways as a result of migratory barriers or elevated susceptibility to infection during spawning migrations in anadromous species.